0.025% Capsaicin Gel for the Treatment of Painful Diabetic Neuropathy: A Randomized, Double‐Blind, Crossover, Placebo‐Controlled Trial. Issue 6 (10th December 2012) - Kulkantrakorn, Kongkiat; Lorsuwansiri, Chakraphong; Meesawatsom, Pongsatorn
Abstract Background Topical therapy may provide additional benefit in patients with painful diabetic neuropathy (PDN). This study was conducted to study the safety and efficacy of 0.025% capsaicin gel in this condition. Methods A 20‐week, double‐blind, crossover, randomized, single‐center study enrolled subjects with PDN. They received 0.025% capsaicin gel or placebo for 8 weeks, with a washout period of 4 weeks between the two treatments. Primary efficacy end point was percent change in visual analog scale (0–100 mm) of pain severity. Secondary outcomes were score change in Neuropathic Pain Scale (NPS), short‐form McGill Pain Questionnaires (SF‐MPQ), proportion of patients who had pain score reductions of 30% and 50%, and adverse event. Results Of the 35 subjects screened, 33 were enrolled and 33 completed at least an 8‐week treatment period. Intention‐to‐treat analysis showed no significant improvement in pain with capsaicin gel, compared with placebo with visual analog scale (VAS) score 28.8 mm vs. 34.6 mm (P = 0.53). No significant difference between the groups was found in SF‐MPQ (7.4 vs. 7.71, P = 0.95), NPS (29.4 vs. 31.3, P = 0.81), and proportion of patients who had 30% or 50% pain relief. Capsaicin gel was well tolerated with minor skin reaction. Conclusions 0.025% capsaicin gel is safe and well tolerated, but does not provide significant pain relief in patients with PDN.